Diagnostics of Primary Immunodeficiencies through Next-Generation Sequencing - Gallo, Vera; Dotta, Laura; Giardino, Giuliana; Cirillo, Emilia; Lougaris, Vassilios; D’Assante, Roberta; Prandini, Alberto; Consolini, Rita; Farrow, Emily G.; Thiffault, Isabelle; Saunders, Carol J.; Leonardi, Antonio; et al. (Frontiers in Immunology, 2016)
Background: Recently, a growing number of novel genetic defects underlying primary immunodeficiencies (PID) have been identified, increasing the number of PID up to more than 250 well-defined forms. Next-generation sequencing (NGS) technologies and proper filtering strategies greatly contributed to this rapid evolution, providing the possibility to rapidly and simultaneously analyze large numbers of genes or the whole exome. Objective: To evaluate the role of targeted next-generation sequencing and whole exome sequencing in the diagnosis of a case series, characterized by complex or atypical clinical features suggesting a PID, difficult to diagnose using the current diagnostic procedures. Methods: We retrospectively analyzed genetic variants identified through targeted next-generation sequencing or whole exome sequencing in 45 patients with complex PID of unknown etiology. Results: 40 variants were identified using targeted next-generation sequencing, while 5 were identified using whole exome sequencing. Newly identified genetic variants were classified into 4 groups: I) variations associated with a well-defined PID; II) variations associated with atypical features of a well-defined PID; III) functionally relevant variations potentially involved in the immunological features; IV) non-diagnostic genotype, in whom the link with phenotype is missing. We reached a conclusive genetic diagnosis in 7/45 patients (~16%). Among them, 4 patients presented with a typical well-defined PID. In the remaining 3 cases, mutations were associated with unexpected clinical features, expanding the phenotypic spectrum of typical PIDs. In addition, we identified 31 variants in 10 patients with complex phenotype, individually not causative per se of the disorder. Conclusion: NGS technologies represent a cost-effective and rapid first-line genetic approaches for the evaluation of complex PIDs. Whole exome sequencing, despite a moderate higher cost compared to targeted, is emerging as a valuable tool to reach in a timely manner a PID diagnosis with a considerable potential to draw genotype-phenotype correlation. Nevertheless, a large fraction of patients still remains without a conclusive diagnosis. In these patients, the sum of non-diagnostic variants might be proven informative in future studies with larger cohorts of patients.